Các thành tạo siêu mafic đới Sông Hồng - Hòa, Trần Trọng; Thế, Nguyễn Văn; Anh, Trần Tuấn; Anh, Phan Lưu; Phượng, Ngô Thị (Vietnam Journal of Earth Sciences, 2000)
Ultramafic rocks in Red river shear zone